Strategi Pemimpin dalam Meningkatkan Mutu Pondok Pesantren Zulhijjah Muara Bulian - Khairunnas Khairunnas; Bawaihi; Nurmia (Management of Islamic Education Department, Faculty of Education and Teacher Training, State Islamic University Sulthan Thaha Saifuddin Jambi, 2021)
This research aims to analyze the strategy of leaders in improving the quality of education in Zulhijjah Muara Bulian boarding school. This research uses descriptive qualitative methods. Data collection is done through observation, interviews, and documentation. Data analysis uses data reduction, data presentation, and drawing conclusions, and verification. The results showed kiai has four roles, in improving the quality of education, namely educators, administrators, managers, and supervisors. Improving the quality of education is done by pursuing the welfare of teachers and contributing thought to the progress of the region and able to become cadres of scholars who will lead the ummah in the future by maintaining educational inputs, processes, and outputs.